Quantum radiation reaction in laser-electron-beam collisions. - Blackburn, T; Ridgers, C; Kirk, J; Bell, A (2014)
It is possible using current high-intensity laser facilities to reach the quantum radiation reaction regime for energetic electrons. An experiment using a wakefield accelerator to drive GeV electrons into a counterpropagating laser pulse would demonstrate the increase in the yield of high-energy photons caused by the stochastic nature of quantum synchrotron emission: we show that a beam of 10(9) 1 GeV electrons colliding with a 30 fs laser pulse of intensity 10(22)  W cm(-2) will emit 6300 photons with energy greater than 700 MeV, 60× the number predicted by classical theory.